The activity notebook in the teaching-learning process of Basic Cuban Geography - Perez , Luis Alfonso; Suárez Sánches , Yamirka; Ferreiro Vázquez , Iliana (Revista Minerva, 2022)
The work corresponds to the pedagogical research carried out at the University of Cienfuegos. It consists of two epigraphs: a first epigraph: The teaching-learning means in the teaching-learning process of the Basic Cuban Geography and its sub-epigraphs and a second epigraph: The teaching-learning means in the teaching-learning process of Basic Cuban Geography and all its description and validation that can effectively contribute to the formation of positive attitudes in students of this level of education, in relation to the performance of the resolution of all the activities proposed in the notebook for a broad development of specific skills of the Geography subject such as the location and location of objects, processes and phenomena that allows them to raise the level of preparation of the students and corroborate the feasibility of the same.